The Dual Mediation Effect Of Job Satisfaction And Stress On Turnover Intention - Dean Herdesvian; Nur Rachmah Wahidah; Noor Arida Sofiana (Eqien - Jurnal Ekonomi dan Bisnis, 2026)
This study examines the configuration of psychological and organizational attributes Job Satisfaction, Job Stress, Organizational Commitment, and Work-Family Conflict that collectively shape employee Turnover Intention. While often studied in pairs or with single mediators, a significant gap exists in understanding how attitudinal and life-domain mechanisms operate in parallel to explain withdrawal behavior. The purpose of this research is to deconstruct and quantify these relationships, specifically evaluating the dual mediating roles of Organizational Commitment and Work-Family Conflict. Employing a quantitative approach, survey data were collected from 38 respondents. Multiple regression analysis tested the direct effects, and parallel mediation analysis was conducted using Hayes’ PROCESS macro. The results revealed that Job Satisfaction significantly reduces Turnover Intention, while Job Stress significantly increases it. Both Organizational Commitment and Work-Family Conflict serve as significant parallel mediators. Organizational Commitment mediates the effects of both Satisfaction and Stress, while Work-Family Conflict specifically mediates the pathway from Job Stress to Turnover Intention. The dual mediation model demonstrates strong explanatory power. A key limitation is the small sample size, which may affect the statistical power and generalizability of the findings. Future research should employ larger, more diverse samples and longitudinal designs to better establish causality and explore potential contextual moderators of these relationships..